New syllabus primary mathematics 4 - Yee, Dr. Foong Pui (Karachi: Oxford University Press., 2024)
New Syllabus Primary Mathematics 4 is a comprehensive textbook aimed at Grade 4 students, designed to deepen their understanding of essential mathematical concepts. The book covers a broad range of topics, including whole numbers, fractions, decimals, geometry, measurement, and data handling. Through clear explanations, worked examples, and engaging activities, the textbook fosters problem-solving abilities and logical reasoning. Each chapter is structured to guide students step-by-step, with practice exercises that reinforce learning. Real-world applications and interactive questions help students connect mathematical concepts to everyday situations, preparing them for more advanced levels of mathematics.